Multimarker Quantitative Real-Time PCR Detection of Circulating Melanoma Cells in Peripheral Blood: Relation to Disease Stage in Melanoma Patients - Koyanagi, Kazuo (2005)
BACKGROUND: Detection of melanoma cells in circulation may be important in assessing tumor progression. The objective of this study was to develop a specific, reliable, multimarker quantitative real-time reverse transcription-PCR (qRT) assay for detecting melanoma cells in patients’ blood. METHODS: We developed qRT assays for the mRNA of four melanoma-associated markers: MART-1, GalNAc-T, PAX-3, and MAGE-A3. In optimization studies, we tested 17 melanoma cell lines and 49 peripheral blood leukocyte (PBL) samples from volunteers. We performed RNA and melanoma cell dilution studies to assess the detection limits and imprecision of the assays. We measured the mRNAs in blood specimens from 94 melanoma patients [American Joint Committee on Cancer (AJCC) stage I, n = 20; II, n = 20; III, n = 32; IV, n = 22]. RESULTS: All markers were frequently detected in melanoma cell lines, whereas none of the markers was detected in PBLs from volunteers. The qRT assay could detect 1 melanoma cell in 10(7) PBLs in the melanoma cell-dilution studies. Markers were detected in 15%, 30%, 75%, and 86% of melanoma patients with AJCC stage I, II, III, and IV disease, respectively. The number of positive markers and AJCC stage were significantly correlated (Spearman correlation coefficient = 0.58; P <0.0001). CONCLUSIONS: Multimarker qRT can detect circulating melanoma cells in blood. Measurement of the studied molecular markers in blood may be useful in detection of metastasis and monitoring treatment response of melanoma patients.